Advances in predicting patient survival in pulmonary sarcoidosis - Kirkil, Gamze; Lower, Elyse; Baughman, Robert (Taylor & Francis Ltd, 2021)
Introduction: Pulmonary disease remains the most common reason for death in sarcoidosis with pulmonary fibrosis and pulmonary hypertension the two most common causes of mortality. Although most sarcoidosis patients with pulmonary fibrosis have a benign outcome, up to 25% of these patients will die from respiratory failure. Unfortunately, over a third of sarcoidosis patients with pre-capillary pulmonary hypertension die within three years. Areas covered: A dedicated search of articles regarding sarcoidosis and survival up to 1 December 2020 formed the basis of the review. Several factors including the extent of pulmonary fibrosis on high-resolution computer tomography (HRCT), the severity of lung impairment on pulmonary function testing including reduction of diffusion of carbon monoxide in the lung (DLCO), and the presence of pulmonary hypertension are associated with an increased risk of death from pulmonary sarcoidosis. A recent composite score has been developed and verified as a useful tool to identify patients at higher mortality risk. Expert opinion: Several features from pulmonary function testing and chest imaging may identify those patients with increased risk for death. Information available from either the HRCT or DLCO alone may provide useful screening data.
Keywords: Mortality; sarcoidosis; pulmonary hypertension; pulmonary fibrosis; hrct; echocardiogram